Biaxial ordering in the supercooled nematic phase of bent-core mesogens: effects of molecular symmetry and outer wing lateral groups. Issue 13 (20th October 2020) - Harkins, Robin; Tauscher, Tatum; Nguyen, Jason; Lewis, Sunny; Adamo, Fabrizio C.; Pisani, Michela; Hermida-Merino, Daniel; Samulski, Edward T.; Vita, Francesco; Francescangeli, Oriano; Scharrer, Eric
ABSTRACT: In previous research, we have found that the incorporation of three lateral substituents on bent-core oxadiazole-based liquid crystals has allowed for the presence of a nematic phase that supercooled to room temperature. X-ray diffraction (XRD) studies of these derivatives have confirmed that the nematic phase consists of cybotactic clusters. Moreover, the wide-angle XRD pattern showed a splitting indicative of local biaxial ordering within this phase. In this paper, we report the phase behaviour of two series of compounds that contain up to four lateral methyl groups. In one series, the arrangement of the lateral groups is symmetrical, and in the other case, the groups are not symmetrically distributed. All of the non-symmetric derivatives supercool to room temperature in the nematic phase, while symmetric derivatives tend to crystallise well above room temperature. XRD analysis of all of these compounds indicates the presence of cybotactic order. However, a splitting of the wide-angle XRD pattern is observed only in derivatives with lateral groups on the outer benzene rings, regardless of their supercooling behaviour, indicating the crucial influence of these substituents on the molecular packing. Graphical abstract: uf0001